2010
DOI: 10.1037/a0017883
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude as moral sentiment: Emotion-guided cooperation in economic exchange.

Abstract: Economic exchange often pits options for selfish and cooperative benefit against one another. Decisions favoring communal profit at the expense of self-interest have traditionally been thought to stem from strategic control aimed at tamping down emotional responses centered on immediate resource acquisition. In the present article, evidence is provided to argue against this limited view of the role played by emotion in shaping prosociality. Findings demonstrate that the social emotion gratitude functions to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
194
5
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(228 citation statements)
references
References 23 publications
10
194
5
5
Order By: Relevance
“…This then would likely increase subsequent generosity as participants in a good mood spread that good mood through generosity. Previous studies have supported this premise, demonstrating that inducing positive emotions like gratitude can increase giving in the laboratory [41].…”
Section: Positive Emotionality In Marathon Participationsupporting
confidence: 51%
“…This then would likely increase subsequent generosity as participants in a good mood spread that good mood through generosity. Previous studies have supported this premise, demonstrating that inducing positive emotions like gratitude can increase giving in the laboratory [41].…”
Section: Positive Emotionality In Marathon Participationsupporting
confidence: 51%
“…Researchers have examined the social contagion effects of prosociality in experimental economic games, and found that generous allocations of resources could indeed spread from person to person (DeSteno, Bartlett, Baumann, Williams, & Dickens, 2010;Fowler & Christakis, 2010;Gray, Ward, & Norton, 2014). In an economic exchange game, for example, participants who had been helped by another gave more money to a stranger than those who had not been helped-a pay-it-forward effect (DeSteno et al, 2010).…”
Section: Who Spreads Prosociality?mentioning
confidence: 99%
“…In an economic exchange game, for example, participants who had been helped by another gave more money to a stranger than those who had not been helped-a pay-it-forward effect (DeSteno et al, 2010). In a multi-round economic game in which participants were constantly changing partners, giving more money to a partner instead of keeping it increased the partner's voluntary donations to others in subsequent rounds (Fowler & Christakis, 2010).…”
Section: Who Spreads Prosociality?mentioning
confidence: 99%
“…As stated previously, experiencing gratitude directly facilitates recognition of a kind act and repayment of the favour. This has been illustrated in controlled lab settings in which feeling grateful leads one to reciprocate with costly helping behaviours (Bartlett & DeSteno, 2006;Tsang, 2006) and to act cooperatively in economic exchanges (DeSteno et al 2010). Hence in our study we wanted to search for the relationship between servant leadership and feelings of gratitude in an organization.…”
Section: Organizational Identificationmentioning
confidence: 99%